(untitled) (Journal of Applied Learning and Teaching, 2023)
Like its predecessor, the Unified Theory of Technology and Use of Technology (UTAUT), UTAUT2 has been adopted, adapted and used in extended forms due to its simplicity, parsimony and robustness. This study synthesised 39 empirical studies based on the UTAUT2 model in educational contexts, using the One-stage Meta-Analysis and Structural Equation Modelling (OSMASEM). Although the findings in this study aligned with the initial findings by Ventakesh et al. (2012), the model did not perform well compared to those in the initial UTAUT2 study in the explained variance in both behavioural intention and use behaviour. When new relationships were introduced into the UTAUT2 model in this study, constructs like performance expectancy, hedonic motivation, social influence, and price value were new predictors of use behaviour. The meta-analytic structural equation modelling approach used in this study, OSMASEM, allows researchers to use past empirical study data to examine the UTAUT2 framework without replicating similar studies. Using OSMASEM, researchers could easily add past empirical data to train the UTAUT2 model to study the trends in technology acceptance and use in educational contexts.